Novel walnut peptide–selenium hybrids with enhanced anticancer synergism: facile synthesis and mechanistic investigation of anticancer activity - Liao W (Dove Medical Press, 2016)
Wenzhen Liao,1 Rong Zhang,1 Chenbo Dong,2 Zhiqiang Yu,3 Jiaoyan Ren11College of Light Industry and Food Sciences, South China University of Technology, Guangzhou, Guangdong, People’s Republic of China; 2Civil and Environmental Engineering, Rice University, Houston, TX, USA; 3School of Pharmaceutical Science, Guangdong Provincial Key Laboratory of New Drug Screening, Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaAbstract: This contribution reports a facile synthesis of degreased walnut peptides (WP1)-functionalized selenium nanoparticles (SeNPs) hybrids with enhanced anticancer activity and a detailed mechanistic evaluation of its superior anticancer activity. Structural and chemical characterizations proved that SeNPs are effectively capped with WP1 via physical absorption, resulting in a stable hybrid structure with an average diameter of 89.22 nm. A panel of selected human cancer cell lines demonstrated high susceptibility toward WP1-SeNPs and displayed significantly reduced proliferative behavior. The as-synthesized WP1-SeNPs exhibited excellent selectivity between cancer cells and normal cells. The targeted induction of apoptosis in human breast adenocarcinoma cells (MCF-7) was confirmed by the accumulation of arrested S-phase cells, nuclear condensation, and DNA breakage. Careful investigations revealed that an extrinsic apoptotic pathway can be attributed to the cell apoptosis and the same was confirmed by activation of the Fas-associated with death domain protein and caspases 3, 8, and 9. In addition, it was also understood that intrinsic apoptotic pathways including reactive oxygen species generation, as well as the reduction in mitochondrial membrane potential, are also involved in the WP1-SeNP-induced apoptosis. This suggested the involvement of multiple apoptosis pathways in the anticancer activity. Our results indicated that WP1-SeNP hybrids with Se core encapsulated in a WP1 shell could be a highly effective method to achieve anticancer synergism. Moreover, the great potential exhibited by WP1-SeNPs could make them an ideal candidate as a chemotherapeutic agent for human cancers, especially for breast cancer.Keywords: selenium nanoparticles, walnut peptides, human cancer cell lines, antiproliferative activity, apoptosis